Lewis Phenotype in Women With Preterm Labor and Premature Rupture of the Membranes - William F. O'Brien; German F. Leparc; Jodi Holbrook (Hindawi Limited, 1995)
Objective: The purpose of this study was to evaluate the possible association between Lewis phenotype status in pregnant women and preterm labor (PTL) or preterm rupture of the membranes (PROM).